The gamma and neutron monitor counters for the MICADO project - Finocchiaro Paolo (EDP Sciences, 2021)
In the framework of the MICADO (Measurement and Instrumentation for Cleaning And Decommissioning Operations) European Union (EU) project, aimed at the full digitization of low and intermediate-level radioactive waste (radwaste) management, a set of 32 solid state thermal neutron detectors, named SiLiF, and 36 gamma-ray counters based on a scintillating fiber readout at each end by a silicon photomultiplier, named SciFi, have been built and characterized. MICADO project encompasses a complete active and passive characterization of the radwaste drums with neutrons and gamma rays, followed by a longer-term monitoring phase. The detectors described are suitable for the monitoring of nuclear materials and can be used around radioactive waste drums possibly containing small quantities of actinides, as well as around spent fuel casks in interim storage or during transportation. Suitable polyethylene moderators, for the SiLiF detectors, can be exploited to better shape the detector response to the expected neutron spectrum, according to Monte Carlo simulations that were performed. The SciFi detectors were thoroughly tested with a 22Na and a 137Cs gamma-ray sources. Both detectors described were tested with an intense AmBe source of neutron and gamma ray. The results are satisfactory and show a quite uniform and reproducible behavior. The next step will be the test in a real environment.